Effect of tin on bandgap narrowing and optical properties of ZnO-Zn2SnO4 electrospun nanofibre composite - Bolarinwa, Hakeem Sanya; Animasahun, Lukman O. (My University, 2020)
The quest for improved visible light absorption in ZnO-based photocatalysts and photodetectors is a prevailing research problem. One method of solving this problem is by narrowing the band gapofthismaterialwellintotherangeofvisiblelightenergy.Inthiswork,wehavedemonstrated considerable band narrowing into the visible region in our electrospun ternary ZnO–Zn2SnO4 nanofibres. We also showed that band narrowing is highly dependent on the amount of Sn in the synthesized composite which could be attributed to the creation of localized states in the ZnO band and the attendant structural changes. However, beyond 15%wt doping there were observed changes in the trend of the bandgap reduction, crystallite sizes, and width of the localized states in the ternary ZnO–Zn2SnO4 band. The details of experimental procedures and discussion of results have been included in this paper.
Keywords: Ternary; tuning effect; fibre; semiconductor; disorderliness; calcination